1995
DOI: 10.1063/1.1145642
|View full text |Cite
|
Sign up to set email alerts
|

Spectrometer for high resolution resonant inelastic x-ray scatteringa)

Abstract: The requirements on the radiation source, the monochromator/mirror, the diffractometer, and the crystal dispersive analyzer for an optimum instrumentation dedicated to high resolution resonant inelastic scattering experiments are formulated. The possibility for the application of dispersion compensation is stressed. A provisional instrumentation at the HARWI–Compton beamline is described and test measurements of the resonant inelastic scattering cross section of Cu for incident photon energies scanning across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Several synchrotrons offer hard x-ray beamlines equipped with high-resolution emission spectrometers. [6][7][8][9][10][11][12][13][14][15][16][17] The spectrometer presented here is installed at the Su-perXAS beamline of the Swiss Light Source. The SuperXAS beamline is equipped with a collimating mirror, followed by a fixed-exit double crystal monochromator to ensure high energy resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Several synchrotrons offer hard x-ray beamlines equipped with high-resolution emission spectrometers. [6][7][8][9][10][11][12][13][14][15][16][17] The spectrometer presented here is installed at the Su-perXAS beamline of the Swiss Light Source. The SuperXAS beamline is equipped with a collimating mirror, followed by a fixed-exit double crystal monochromator to ensure high energy resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it allows Cu + and Cu 2+ to be distinguished unambiguously. 23,24 With recent instrumentation development, 22,[25][26][27][28][29][30][31][32][33][34][35][36] few synchrotrons made the HERFD XAS technique available to the XAS community. Applications of HERFD XAS to catalysis include the study of Fe/ZSM-5 by Heijboer et al, 37 Mn/ZSM-5 by Radu et al, 38 Au/Al 2 O 3 by van Bokhoven et al, 39 and Pt/Al 2 O 3 by Singh et al 40 The aim of the experiment reported is to evaluate the state of the Cu/ZnO/Al 2 O 3 catalyst under reaction conditions, which is achieved with operando HERFD XAS at realistic temperature, pressure, and reaction gas mixture composition.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence light emitted during the decay process can be recorded using a secondary crystal analyzer with an energy bandwidth similar to that of the primary monochromator of the synchrotron beamline. [37][38][39] The process can be viewed as an inelastic scattering of the incident photon at the Mn atom and is theoretically described by the Kramers-Heisenberg formula: 40,41 This description is analogous to optical resonance Raman spectroscopy. 42,43 The intermediate state |n〉 is reached from the ground state |g〉 via a transition operator T 1 .…”
Section: Introductionmentioning
confidence: 99%